2019
DOI: 10.1016/j.jacbts.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Induces Remote Cardiac Damage and Dysfunction Through the Galectin-3 Pathway

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 40 publications
6
45
0
2
Order By: Relevance
“…Similarly, as advanced by Prud’homme et al. (1), AKI, through circulating hormones or mediators, induces cardiac injury and dysfunction. The current Gal-3 inhibition studies, however, did not demonstrate noticeable improvement on renal function (creatinine and blood urea nitrogen levels) or renal hypertrophy, although significant improvements were observed in cardiac parameters.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Similarly, as advanced by Prud’homme et al. (1), AKI, through circulating hormones or mediators, induces cardiac injury and dysfunction. The current Gal-3 inhibition studies, however, did not demonstrate noticeable improvement on renal function (creatinine and blood urea nitrogen levels) or renal hypertrophy, although significant improvements were observed in cardiac parameters.…”
mentioning
confidence: 83%
“…Here in this elegantly designed study, Prud’homme et al. (1) demonstrated that Gal-3 can serve as both a drug target for AKI-induced cardiac dysfunction and a biomarker for AKI.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Epidemiologic studies have found an association between serum Gal-3 level and risk of sepsis [20][21][22] as well as development of chronic kidney disease (CKD) [23][24][25]. Pertinent ndings show that serum Gal-3 predicts 30-day all-cause mortality in sepsis [26], preoperative serum Gal-3 predicts AKI after cardiac surgery [27], and serum Gal-3 at ICU discharge is associated with severity of AKI [28]. However, no previous study has examined the relationship between serum Gal-3 at the time of admission and the subsequent development of AKI in patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%